Composite fabrication by slip-casting - Tan, Sharlene (Nanyang Technological University, 2020)
This project aims to explore the use of ceramics in the electronics industry, as well as investigating the use of slip-casting to manufacture ceramic-polymer composites with an unusually high concentration in ceramics. The project compares the current materials used industrially and proposes the use of hexagonal boron nitride (h-BN) and silicon dioxide (SiO2) as solid fillers in an epoxy matrix. With such composition, the composite is expected to exhibit a higher thermal conductivity than current materials used in electronic packaging. The specific objective of the project is to determine which ratio of h-BN : SiO2 : water could realize simultaneously low viscosity and high solid loading after slip-casting. In this report are descriptions of the sample processing, the characterization of their density and porosity as a function of the BN and SiO2 loadings, the infiltration process with an epoxy matrix and Vickers hardness test. The results are discussed, and future research steps determined.